Role and place of intra-regional cooperation in the framework of future ACP-EU relations - Pangeti, Evelyn S (ECDPM MaastrichtNL, 1997)
Sees regional economic integration as the main route towards the restructuring of ACP economies away from traditional primary exports, away from heavy dependence on EU markets, and towards new and more sustainable, as well as competitive production and marketing structures. Notes that the EU is a major player in the drive to promote regional integration within the ACP.